2009
DOI: 10.1021/nl802580r
|View full text |Cite
|
Sign up to set email alerts
|

Large Photonic Strength of Highly Tunable Resonant Nanowire Materials

Abstract: We demonstrate that highly tunable nanowire arrays with optimized diameters, volume fractions, and alignment form one of the strongest optical scattering materials to date. Using a new broad-band technique, we explore the scattering strength of the nanowires by varying systematically their diameter and alignment on the substrate. We identify strong Mie-type internal resonances of the nanowires which can be tuned over the entire visible spectrum. The tunability of nanowire materials opens up exciting new prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 30 publications
1
118
0
1
Order By: Relevance
“…67 If C PS is low, l free becomes larger than L; hence, k goes to unity, and the system is no longer in the multiscattering regime. Figure 6A displays both measured and simulated k values as a function of F for phenol red.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…67 If C PS is low, l free becomes larger than L; hence, k goes to unity, and the system is no longer in the multiscattering regime. Figure 6A displays both measured and simulated k values as a function of F for phenol red.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9(a) and 9(b) for four different samples with scattering strength ranging from k e B = 26 ± 3 to k e B = 3.6 ± 0.8. most strongly scattering nanowire material of Ref. 22. CBS cones (ii) and (iii) in Fig.…”
Section: B Frequency Correlations In Coherent Backscatteringmentioning
confidence: 95%
“…In addition, we also include in our studies two layers of GaP nanowires, which have been shown to be among the most strongly scattering nanomaterials available today. 22 …”
Section: Methodsmentioning
confidence: 99%
“…This procedure increased the homogeneity of the layer and reduced the alignment (see Supplementary Section S1). Such compressed semiconductor nanowire mats were shown to be one of the most strongly scattering materials in the visible wavelength range 18 .…”
mentioning
confidence: 99%